EFEKTIVITAS EKSTRAK WRESAH (AMOMUM DEALBATUM) DALAM MENGHAMBAT PERTUMBUHAN STAPHYLOCOCCUS AUREUS - Ajeng Dian Pertiwi; Musparlin Halid (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Wresah plant (Amomum dealbatum) is one of the typical fruit species from Lombok Island which has a distinctive fragrance and is a member of the ginger-ginger tribe. This study aims to test the ethanol extract of Wresah skin (Amomum dealbatum) as an antibacterial (Staphylococcus aureus) with concentrations of 15%, 30% and 50%. The research method conducted was laboratory experimental. The antibacterial test of Staphyloccocus aureus was carried out with five treatment groups and five repetitions, namely positive control (ciprofloxacin), negative control (distilled water), concentrations of 15%, 30% and 50% using well method and then incubated for 24 hours at a temperature of 370 C. The results of the antibacterial test of ethanol extract of Wresah fruit peel showed inhibition of Staphylococcus aureus bacteria and at concentrations of 15%, 30%, and 50% which produced the largest diameter of the inhibition zone with an average diameter of 2.0 mm. The Kruskal Wallis test showed a statistically significant difference between the three concentrations tested (p < 0.05), which means that Wresah fruit peel extract is able to inhibit the growth of Staphylococcus aureus bacteria. In conclusion, the extract of Wresah fruit peel has demonstrated antibacterial properties against Staphylococcus aureus and can be used as a natural alternative to conventional antibiotics.